Monte Carlo study of phase separation in magnetic insulators - Murawski, Szymon; Kapcia, Konrad Jerzy; Pawłowski, Grzegorz; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, PL-02-668 Warsaw, Poland, 2015)
In this work we focus on the study of phase separation in the zero-bandwidth extended Hubbard with nearest-neighbors intersite Ising-like magnetic interactions $J$ and on-site Coulomb interactions U. The system has been analyzed by means of Monte Carlo simulations (in the grand canonical ensemble) on two dimensional square lattice (with N=LxL=400 sites) and the results for U/(4J)=2 as a function of chemical potential and electron concentration have been obtained. Depending on the values of interaction parameters the system exhibits homogeneous (anti-)ferromagnetic (AF) or non-ordered (NO) phase as well as phase separation PS:AF/NO state. Transitions between homogeneous phases (i.e. AF-NO transitions) can be of first or second order and the tricritical point is also present on the phase diagrams. The electron compressibility $K$ is an indicator of the phase separation and that quantity is of particular interest of this paper.
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A.
Keywords: extended Hubbard model; atomic limit; magnetism; phase separation; Monte Carlo simulations